Anti-torque systems of electromechanical cable-suspended drills and test results. Issue 68 (2014) - Talalay, Pavel; Fan, Xiaopeng; Zheng, Zhichuan; Xue, Jun; Cao, Pinlu; Zhang, Nan; Wang, Rusheng; Yu, Dahui; Yu, Chengfeng; Zhang, Yunlong; Zhang, Qi; Su, Kai; et al.
Abstract: To prevent spinning of the upper non-rotated part of the electromechanical drill, an 'anti-torque system' has to be included in the downhole unit. At the same time, the anti-torque must allow the drill to move up and down the borehole during drilling and tripping operations. Usually the anti-torque system has a blade form of various designs that engages with the borehole wall and counteracts the torque from the stator of the driving motor. This paper presents a review of the different anti-torque systems and test results with selected designs (leaf spring, skate and U-shaped anti-torque systems). Experiments showed that the skate anti-torque system can provide the maximal holding torque between 67 and 267 Nm −1 depending on the skates' outer diameter and ice temperature, while the leaf spring anti-torque system can provide only 2.5–40 N m −1 (in case of straight contact between the ice and the leaf springs). The total resistance force to axial movement of the skate anti-torque system lies in the range 209–454N if the system is vibrating. For the leaf spring anti-torque system, the total axial resistance force is far less (19–243 N).